Ficções: arte, natureza, cidade - Ines Karin Linke Ferreira (2012)
This thesis builds on the concepts of public art, contextual art and the perception of spaces and also approaches the city and nature as aesthetic fields, objects of knowledge and artistic media. It focuses on the strategies of the artistic group Thislandyourland that performs actions related to local daily practices. Projects like Life without party rooms, Tourism, Bike Foods and Garden Wall are part of the work so as to show and articulate different notions of autonomy and engagement practicedinside and outside the art system. Furthermore, it relates the experience of places in creation processes based on contexts, situations and existing spaces, in order to present data and information from different areas of knowledge, which contribute to the debate in the field of arts. It establishes a discussion of works of other artists, approaches strategies that denounce the systematic reduction of experience and creates a reflection on the social function and the political dimensions ofcontemporary art.